Capital Transfers and External Balance in Post-Accession Poland - Andrzejczak, Monika (Studia Oeconomica Posnaniensia, 2019)
Poland's accession to the EU in 2004 resulted in changes in the external conditions influencing the functioning of the domestic economy. The balance of payment structure changed, together with the role of the capital account. Capital transfers in the form of investment grants became a major category of revenues in the capital account. The aim of this article is to show the capital account changes in terms of external balance indicators after 2004 and to verify a hypothesis concerning the impact of a positive capital account balance on the improvement of the said indicators. The research problem pertains to the role of capital transfers with reference to the balance of payments theories, external balance indicators and domestic investments. The adopted research method consisted of a statistical data analysis with the use of dynamics indicators, as well as literature studies on the balance of payments theories. The obtained results of the research shows that capital transfers filled the gap arising from the lack of domestic savings and did not exclude the positive impact of capital transfers on the improvement of the Polish external imbalance level.